The Effect of Asset Valuation Method, Auditor Quality, Characteristics of the Board Commissioners and Audit Committee on Stock price Synchronicity - Putri, Arrin Insani; Butar, Sansaloni Butar (Jurnal Akuntansi Bisnis, 2024)
Stock price synchronicity refers to the extent to which firm-specific information is absorbed in stock prices relative to market-wide information. If return variations are more synchronized with market information, then stock price synchronicity decreases which is indicating lower quality of financial reports. This research examines the effect of asset valuation methods, auditor quality, characteristics of the Board of Commissioners and the Audit Committee on the synchronicity of stock price of manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. A total of 490 observations were available for hypothesis testing. The results show that the quality of the auditor and the size of the Board of Commissioners have negative effects on stock price synchronicity. On the other hand, the asset valuation method, the independence of the Board of Commissioners and the Audit Committee have no effect on stock price synchronicity of. The practical contribution of this research is that companies need to consider hiring more commissioners and Big Four accounting firms to increase the credibility of financial reports.